Analisis Kuat Tekan Beton Dengan Variasi Pecahan Genteng Sebagai Agregat Kasar Dan Abu Sekam Padi Sebagai Agregat Halus - Gusti Yawan; Yudi Setio Prabowo; Muhammad Oka Mahendra (Jurnal Konstruksi, 2025)
Analysis of Concrete Compressive Strength with Variations in Roof Tile Fragments as Coarse Aggregate and Rice Husk Ash as Fine Aggregate Concrete is a widely used construction material due to its compressive strength and availability of raw materials. However, the limited availability of natural aggregates has led to the use of alternative materials from waste. This study aims to analyze the effect of using broken tiles as a substitute for coarse aggregate and rice husk ash as a substitute for fine aggregate on the compressive strength of K-175 grade concrete. The mixture variations used included normal concrete, concrete with 7% broken tiles and 1.5% rice husk ash, and concrete with 9% broken tiles and 3% rice husk ash. The test specimens, which were 15×15×15 cm cubes, were tested for compressive strength at 7 and 21 days of age in accordance with SNI standards. The test results showed that the use of tile fragments and rice husk ash tended to reduce the compressive strength of concrete compared to normal concrete. At 7 days, normal concrete had an average compressive strength of 9.5 MPa, while the mixture of 7% broken tiles + 1.5% rice husk ash decreased to 6.6 MPa, and the mixture of 9% broken tiles + 3% rice husk ash decreased to 6.0 MPa. At 21 days, the compressive strength of normal concrete reached 12.4 MPa, while the 7% + 1.5% mixture was only 10.7 MPa, and the 9% + 3% mixture was 8.4 MPa. Thus, the higher the percentage of waste substitution used, the greater the decrease in concrete compressive strength.